Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca